The Journal to Stella - Swift, Jonathan, 1667-1745; Aitken, George Atherton, 1860-1917 (Salt Lake City, UT : Project Gutenberg, 2003)
"The Journal to Stella" by Jonathan Swift is a collection of letters written in the early 18th century, focusing on the correspondence between Swift and his close friend Esther Johnson, affectionately known as Stella. The journal highlights their unique friendship, capturing a rich blend of personal reflections, daily observations, and various societal contexts in which Swift found himself. Through these letters, readers can glean insights into Swift's thoughts on his life, his whimsical yet serious nature, and the intertwining of his public interactions with private affections. At the start of the correspondence, Swift details his journey to London and the initial encounters he has with various notable figures. He shares observations on the political atmosphere and personal relationships while expressing a sense of longing for Stella's company. The opening letters illustrate his day-to-day activities and concerns regarding both professional matters and personal affections, including updates about their mutual acquaintances and agile commentary on the political landscape. Through these early exchanges, readers are introduced to Swift's candid writing style and his nuanced affections for Stella, setting the stage for the deeper exploration of their bond throughout the journal. (This is an automatically generated summary.)
Wikipedia page about this book: https://en.wikipedia.org/wiki/A_Journal_to_Stella
Release date is 2003-07-01
This eBook was produced by Les Bowler
Keywords: Johnson, Esther, 1681-1728 -- Correspondence; Swift, Jonathan, 1667-1745 -- Correspondence; Authors, Irish -- 18th century -- Correspondence